Into the Mist - Carman, Patrick (New York : Scholastic Press, 2007)
Captain Roland Warvold tells Alexa and Yipes about the adventures he shared with his brother Thomas in Elyon, before the wall went up and divided the world in two.
Keywords: Fiction; Magic -- Fiction; Brothers -- Fiction; Orphans -- Fiction